Long-Term storage of Tularemia Agent strains - V. Yu. Okhapkina (Проблемы особо опасных инфекций, 2018)
Keeping microorganisms alive, saving initial practically vital properties, is a major issue in microbiology. Objective of this research was to study preservation of the key biological properties of lyophilized cultures of 18 F. tularensis strains of different subspecies from the cultures collection of the «48 Central Research Institute» of the Ministry of Defense of the Russian Federation under varying conditions of preliminary preparation (including animalization through the guinea pigs’ body or without it). The microbe storage life at below-freezing temperatures ranged from 5 to 50 years. Materials and methods. The survival of microbes in the process of drying and subsequent storage was determined in accordance with the commonly-accepted methods; morphological, cultural, biochemical, antigenic, and pathogenic properties of F. tularensis strain cultures with different storage term and conditions for preparation to lyophilization were assessed and compared with datasheet specification. The results and conclusions. The research showed that under preliminary stabilization of F. tularensis strain properties using animalization, the storage in lyophilized state at below-freezing temperatures under vacuum for up to 50 years or less protected them from changes in phenotypic properties. At the same time, after lyophilization of cultures, which were repeatedly sub-cultured on dense nutrient media without initial signs of properties’ breach, phenomena of dissociation, the decrease in titers of cultures in the agglutination reaction from 2 to 4 times, and an increase in LD50 index by times were found.